Feira de Macaíba/RN : um estudo das modificações na dinâmica socioespacial (1960/2006) - Dantas, Geovany Pachelly Galdino (2007)
The objective of the current piece of research is to reflect upon the diverse changes that have occurred in the social and spatial dynamics of the Macaíba fair in the period between 1960 and 2006. During the second half of the 19th century, Macaíba had in the commerce one of this principle economic base a contribution for which the city became one of the main commercial warehouses of the East coast of the Rio Grande do Norte region. This helped lead to the growth of Macaíba s fair, which proved to be one of the most important existing in the state until the 1970 s. In the last two decades of the 20th century, certain elements represented challenges to the fair at Macaíba. These challenges stimulated substantial changes in the fair s dynamics which include the growth and expansion of the commercial and service sector, primarily though supermarkets; consolidation among the commercial and distribution networks, represented by the Central Office of Supply of the Rio Grande do Norte S/A (Ceasa/RN), by the wholesale and refrigeration companies; and the modernization of transportation methods, which permitted an expanded reach for these networks. Even with all these changes, the fair continues to be one of the strongest aspects of the city being the center of resistance against the surge of new forms of commerce and consumption in the city (notable the supermarkets) and the diffusion of other aspects of globalization. The fair has economic importance, as it offers a popular marketplace for the commercialization of very different products and a means for supplying goods to the residents of the city and the rural communities of Macaíba and the surrounding municipalities; and socio-cultural importance in that the fair is a place where popular tradition is expressed, a place where a great number of parallel activities occur, a place for meeting again and again, of conversations, of manifestations of culture and art, and of socialization in all of its dimensions